Transits between Psychology and the art of Ana Mendieta: gender violence and other becomings - Gorjon, Melina [UNESP]; Galindo, Dolores; Milioli, Danielle [UNESP] (Univ Autonoma Barcelona, Dept Psicologia Salut, 2018)
Throughout the essay, we read the work of the Cuban artist Ana Mendieta from the contributions of the modernity/coloniality movement and the thought of difference to propose a transdisciplinary look at the themes of gender violence and naturalizing conceptions of gender. The research in Psychology finds in the performances of Ana Mendieta an intercessor for the production of knowledge about the feminist art of nonwhite, exiled, asylum women. We discussed two performances by Ana Mendieta as resistances to the colonialities of gender, race, and ethnicity. It is not the whole of Contemporary Art that breaks with colonialist practices, since the daily work of creation in art is carried out in a constant deal with captures by colonialist-capitalist practices. The art of Mendieta allows us to think of colonialities present in Psychology. The potentialities of transdisciplinarity between Social Psychology and Contemporary Art show a process of mutual contamination that questions knowledge and practices
Keywords: Psychology; Art; Decoloniality